e-INEBRIA Special Interest Group Roadmap for Best Practices for Research on Brief Digital Interventions for Problematic Alcohol and Illicit Drug Use - Schaub, Michael Patrick; Berman, Anne H; López Pelayo, Hugo; Boumparis, Nikolaos; Khadjesari, Zarnie; Blankers, Matthijs; Gual, Antoni; Riper, Heleen; Pas, Lodewijk (JMIR Publications, 2020)
There is great potential for scaling up the delivery of brief interventions for alcohol and illicit drug use, given the increasing coverage of mobile devices and technologies for digital interventions, including apps for smartphones and tablets. However, while the number of digital interventions is increasing rapidly, the involvement of brief-intervention researchers and the development of good practices has just begun. In 2018, the Special Interest Group on digital interventions of the International Network on Brief Interventions for Alcohol & Other Drugs (e-INEBRIA SIG) initiated a conversation regarding possible avenues of future research, which subsequently became a roadmap for digital interventions. This roadmap consists of points considered relevant for future research, ongoing technological developments, and their implementation across a continuum of prevention and care. Moreover, it outlines starting points for the diversification of brief digital interventions, as well as next steps for quality improvement and implementation in public health and clinical practice. The roadmap of the e-INEBRIA SIG on digital interventions is a starting point that indicates relevant next steps and provides orientation for researchers and interested practitioners with regard to the ambiguous literature and the complexity of current digital interventions.